Cellulolytic and xylanolytic activities of common indoor fungi. (February 2016) - Andersen, Birgitte; Poulsen, Rehab; Hansen, Gustav H.
Abstract: Moldy building materials, such as chip wood and gypsum, should be a good source for fungal strains with high production of lignocellulolytic enzymes. Screening of 21 common indoor fungal strains showed, contrary to the expected, that the Chaetomium and Stachybotrys strains had little or no cellulolytic and xylanolytic activities using AZCL-assays. On the other hand, both Cladosporium sphaerospermum and Penicillium chrysogenum showed the highest cellulase, β-glucosidase, mannase, β-galactanase and arabinanase activities and would be good candidates for over-producers of enzymes needed to supplement industrial enzyme blends or boost the bioconversion of lignocellulose-rich biomass. Highlights: Enzyme activities of common indoor fungi. Chaetomium and Stachybotrys showed little enzyme activity. Cladosporium and Penicillium showed high enzyme activities.